Penerapan Model Pembelajaran Jigsaw Combination Windows Shopping (JCWS) Terhadap Peningkatan Hasil Belajar - Prasetyo, Angga Dwi (Universitas Nusantara PGRI Kediri, 2020)
The learning process is carried out to achieve educational goals, one of which can support the achievement of educational goals is the learning model used during the learning and teaching process, many learning models are often used by teachers in the learning process and teaching, one of which is the jigsaw type learning model and the windows shopping learning model. . Indonesia is included in the lowest ranking in the category of scientific literacy and scientific ability based on the Trends In International Mathematics and Science Study (TIMSS) and Program for International Student Assessment (PISA) scores in 2018, so a learning model is needed that is in accordance with the science material given at the time of learning. . The purpose of this study is to look at the application of the jigsaw and windows shopping combination learning model on learning completeness and improving student learning outcomes, the method used is quassy experiment with purposive sampling and data analysis using the N-gain test. The results showed that the jigsaw combination windows shopping (JCWS) learning model on basic science concepts could increase learning outcomes by 0.79 which was included in the high category compared to the control class by 0.69. The application of the JCWS learning model can increase the number of students' learning mastery. Based on the results of the study, it was found that the JCWS learning model can improve student learning outcomes on the basic concepts of science.